Efektivitas Metode Restrukturisasi Kognitif Terhadap Kepercayaan Diri Remaja di SMA Negeri 1 Gunungsitoli - Telaumbanua, Vivid Anggreni; Damanik, Hosianna R.; Zebua, Elizama; Lase, Justin F. (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Self-confidence is one aspect of personality that is important in a person. Without self-confidence, it will cause many problems in a person. Self-confidence is the most valuable attribute in a person in community life, therefore the author is interested in discussing the problem with the title Effectiveness of Cognitive Restructuring Methods on Adolescent Self-Confidence at SMA Negeri 1 Gunungsitoli. The purpose of the study was to determine whether the Cognitive Restructuring Method is Effective for Self-Confidence in Adolescents at SMA Negeri 1 Gunungsitoli. The research design used was a quasy experiment. The research sample was class XI-MIPA 3 students as an Experimental Class with a total of 31 people and class XI-IPS 2 as a Control Class with a total of 31 students. The results showed that the results of the final test (post-test) that had been carried out, obtained a percentage of confidence in the Experimental Class which was 87.20% with Good criteria. Furthermore, the percentage of student confidence in the Control Class was 54.84% with the criteria of Less. In accordance with the data of the final test results (post-test) described above, it can be concluded that confidence in the Experimental Class has increased well compared to confidence in the Control Class which is still relatively sufficient.